Zakat and Shared Prosperity: Framework for Sustainable Society - Afifi, Abdullah A (IDRIS Darulfunun Institute, 2025)
This study aims to construct a conceptual framework that explains how zakat contributes to shared prosperity and supports the development of a sustainable society. It seeks to model measurable links between zakat distribution and key social-sector indicators, such as poverty, education, employment, health, and household welfare, using the available national indicators. The study builds a conceptual framework that integrates zakat and shared prosperity within sustainability theory. The zakat is effective in reducing vulnerabilities and promoting shared prosperity within four objective indicators, which are reduced poverty, better education, improved health, and economic inclusion. This study is primarily conceptual, and therefore, it needs further simulated empirical modelling on the availability and quality of real-world datasets. Many national statistics data variables are not directly relevant as data sources for zakat impact, which can lead to more integrated data available for shared prosperity. The results can assist zakat institutions in improving targeting accuracy, designing evidence-based intervention programs, and aligning zakat distribution with national poverty-reduction strategies. Policymakers may use the framework to integrate zakat into broader social protection systems and data integration. By demonstrating how zakat contributes to shared prosperity, the study reinforces zakat’s role in reducing inequality, strengthening social cohesion, and enhancing the welfare of vulnerable groups. It also promotes a sustainable society where economic justice and moral responsibility converge. This study offers a unique combination of conceptual theory and empirical modelling for zakat effectiveness, supported by a measurable framework tied to national indicators. It is among the first to propose a scalable zakat–shared-prosperity model, enabling future studies to replicate, refine, and apply the approach in policy and institutional settings.